PENGEMBANGAN MEDIA TUTORIAL BERBASIS MULTIMEDIA INTERAKTIF PADA MATERI LISTRIK DINAMIS - Anggit Wikcaksono; Agus Suyatna; Feriansyah Sesunan (Jurnal Pembelajaran Fisika, 2013)
Observations and interviews show that in Xaverius Pringsewu High School have the facilities and infrastructure that support the learning process, but its are not used optimally. Added with the problems that appear on the material electricity dynamic, the percentage of students who did not complete the material electricity dynamic at class X in 2011/2012 which is up to 91.6%. Based on the state of media researchers to develop interactive multimedia based tutorial material on high school physics electricity dynamic. This research uses research and development which refers to the procedure of learning instructional media development by Sadiman which includes seven procedures, namely: analysis of the needs and characteristics of students, formulate learning objectives, formulate particle of materials, prepare an evaluation instrument, prepare the manuscript or draft media, perform validation expert, trial or test and revision. Expert validation test results indicate that the media has been developed in accordance with theory and fit for use as a medium of learning. Field test results show that developed media tutorial is very interesting, very easy to use and useful, and effective use as a medium of learning electricity dynamic.Keywords: research development, media tutorials, and electricity dynamic.